PERAN PENDAMPING SOSIAL DALAM DALAM MENDUKUNG PELAKSANAAN PROGRAM KESEJAHATERAAN SOSIAL - Khuriyatul Husna; Aguswan Aguswan; Muhammad Sawalludin; Fajarwaty Kusumawardhani; Dwi Herlinda; Iwan Tanjung Sutarna (Ensiklopedia of Journal, 2023)
This article explains the role of social assistants in community empowerment. Social assistants are needed as part of the direct and indirect determinants of the success of implementing community empowerment programs. The community becomes empowered by the assistance provided by social assistants so that the community can rise and achieve social welfare. To understand the role of the social assistant, a qualitative approach was used in this study. The study results show that the role of social assistants in community empowerment is good by being a facilitator, broker, mediator, defender, and protector. However, the role of the assistant in the field also plays a role as a liaison, motivator, researcher, mobilizer, advocate, evaluator, and mentor. The role played has not been maximized to empower the community due to social assistants carrying out their role difficulties in monitoring movements by the need for social welfare services, lack of cooperation and a sense of care between community leaders, and comprehensive coverage of work areas.